(3Gdbhi GdWHjYjIs - (3LGdjfhSs ((3eMeO Hf CMeO Hf eMeO s)
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3Efg deG cGf GdMS hGdMQcI GdEQGOjI NGUjf HGdMjhGf , hGdfehQ hGdJZPi YGejf ddMjhGf hGdfHGJ s
(3BNQgG (B:s
(3aEPG cGf ai CaVjI GdYQhb GdVhGQ HNGQ hghGA hOe dWja de JLJPH ef GdCNdGW GdeMJSHI ai GdeYOI hGdCeYGA TjFG k CUdG, Ch cGf eG JLJPHg TjFkG jSjQkG LOkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B54s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B188 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(848) s
Keywords: (3GdWHs